Conspiracy mentality and political orientation across 26 countries - Imhoff, Roland; Zimmer, Felix; Klein, Olivier; António, João H C; Babinska, Maria; Bangerter, Adrian; Bilewicz, Michal; Blanuša, Nebojša; Bovan, Kosta; Bužarovska, Rumena; Cichocka, Aleksandra; Delouvée, Sylvain; et al. (Nature human behaviour, 2022)
People differ in their general tendency to endorse conspiracy theories (that is, conspiracy mentality). Previous research yielded inconsistent findings on the relationship between conspiracy mentality and political orientation, showing a greater conspiracy mentality either among the political right (a linear relation) or amongst both the left and right extremes (a curvilinear relation). We revisited this relationship across two studies spanning 26 countries (combined N = 104,253) and found overall evidence for both linear and quadratic relations, albeit small and heterogeneous across countries. We also observed stronger support for conspiracy mentality among voters of opposition parties (that is, those deprived of political control). Nonetheless, the quadratic effect of political orientation remained significant when adjusting for political control deprivation. We conclude that conspiracy mentality is associated with extreme left- and especially extreme right-wing beliefs, and that this non-linear relation may be strengthened by, but is not reducible to, deprivation of political control.